Exploring the Anti-Bildungsroman in Kopano Matlwa’s Coconut (2007) and Adaobi Tricia Nwaubani’s I Do Not Come to You by Chance (2009) - Shirinde, Karabelo (University of the Witwatersrand, Johannesburg, 2024)
This study uses the term anti-bildungsroman to reference African post-colonial counter-discursive novels that reconfigure the conventions of the classical bildungsroman. The anti-bildungsroman allows post-colonial writers to ‘talk back’ to empire by claiming narrative forms and structures that have historically centred the bourgeois white male protagonist. This research study explores how the anti-bildungsroman centres post-colonial protagonists’ coming of age in environments deeply affected by colonialism. The study examined the extent to which the coming-of-age novels Coconut (2007) by Kopano Matlwa and I Do Not Come to You By Chance (2009) by Adaobi Tricia Nwaubani reconfigure the traditional bildungsroman format to constitute an African counter discourse. The study examines themes tied to the protagonists’ social condition that influence their environment and shaped their daily experiences; the narrative structure and characterology which determined how the structural plots and goals of socialisation are reconfigured; and the historical, socio-political and cultural contexts in which the respective narratives are set, which take into consideration the history of colonialism, contemporary impacts of neoliberalism, and the struggles of nation-building within post-independent states. The study concludes that Coconut (2007) and I Do Not Come to You By Chance (2009) are forms of anti-bildungsroman which express the challenges associated with coming of age in countries stained by the ramifications of colonialism. Matlwa and Nwaubani reject the ideological premises of the classical bildungsroman genre which is tied to European bourgeois subjectivity. Instead, they reconfigure the classical coming of age story in the context of the aftermath of empire.
A research report Submitted n partial fulfillment of the requirements for the degree Master of Arts in African Literature, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Anti-Bildungsroman; Bildungsroman; Coconut (2007); I Do Not Come to You by Chance (2009); SDG-4: Quality education